MiR‐4756 promotes albumin‐induced renal tubular epithelial cell epithelial‐to‐mesenchymal transition and endoplasmic reticulum stress via targeting Sestrin2. Issue 3 (26th August 2018) - Jia, Yijie; Zheng, Zongji; Yang, Yanlin; Zou, Meina; Li, Jimin; Wang, Ling; Guan, Meiping; Xue, Yaoming
Abstract : Accumulating evidence indicates that proteinuria promotes the progression of diabetic kidney disease (DKD) and induces renal epithelial tubular cell epithelial‐to‐mesenchymal transition (EMT) and endoplasmic reticulum (ER) stress, but the mechanism remains unclear. In our previous research, we found that miR‐4756 levels were increased in the urinary extracellular vesicles of type 2 diabetes mellitus patients with macroalbuminuria. In a preliminary study, we found that miR‐4756 may be derived from renal tubular epithelial cells, but its role has not been elucidated. Albumin stimulation significantly increased miR‐4756 levels in HK‐2 cells. In addition, an miR‐4756 mimic accelerated albumin‐stimulated HK‐2 cell EMT and ER stress, and an miR‐4756 inhibitor suppressed these events. We then found that miR‐4756 targeted the 3′‐untranslated region (UTR) of Sestrin2 and directly suppressed Sestrin2 expression. Furthermore, the induction of EMT and ER stress by the overexpression of miR‐4756 was abolished by Sestrin2 overexpression. Moreover, the overexpression of miR‐4756 increased ERK1/2 activation and decreased 5′ monophosphate‐activated protein kinase activation. Thus, our study provides evidence that miR‐4756 accelerates the process of DKD through Sestrin2, suggesting that targeting miR‐4756 may be a novel strategy for DKD treatment. Abstract : MiR‐4756 exerts its effect by targeting Sestrin2, which inhibits renal epithelial‐to‐mesenchymal transition and endoplasmic reticulum stress during diabetic kidney disease (DKD). MiR‐4756 content was also increased in urinary extracellular vesicles of DKD patients and extracellular vesicles derived from human serum albumin‐treated HK‐2 cells, which indicated that miR‐4756 in urinary extracellular vesicles may reflect the pathophysiological changes during DKD.